New species of the Rhinella crucifer group (Anura, Bufonidae) from the Brazilian Cerrado - Vaz-Silva, Wilian; Valdujo, Paula Hanna; Pombal Jr., José P. (Zootaxa, 2012)
A new species of Rhinella of Central Brazil from the Rhinella crucifer group is described. Rhinella inopina sp. nov. is restricted to the disjunct Seasonal Tropical Dry Forests enclaves in the western Cerrado biome. The new species is characterized mainly by head wider than long, shape of parotoid gland, and oblique arrangement of the parotoid gland. Data on natural history and distribution are also presented.